Assessment of left atrial function by strain in patients with acute ıschemic stroke left atrial function and acute stroke - Ozturk,Unal (2021)
SUMMARY OBJECTIVE: Myocardial speckle-tracking echocardiography can detect subtle abnormalities in the left atrial function. In this study, we aimed to investigate the relationship between left atrial myocardium and tissue function n assessed by two-dimensional speckle-tracking echocardiography and the National Institutes of Health Stroke Scale score in patients with acute ischemic stroke. METHOD: The study was composed of 80 patients (45 men, 35 women, mean age: 67±15 years) with acute ischemic stroke. The patients were divided into two groups based on the calculated National Institutes of Health Stroke Scale score (group 1, National Institutes of Health Stroke Scale score < 16; group 2, National Institutes of Health Stroke Scale score ≥ 16). Demographic, clinical, and laboratory data for all patients were collected. Cardiac functions were evaluated using two-dimensional speckle-tracking echocardiography within 48 hours from admission to the neurology care unit. RESULTS: There were no significant differences between the patients’ clinical parameters. Left ventricular ejection fraction was significantly higher in group 1 than in group 2 (59.2±5.6 to 51.4±6.3, p=0.024). Left atrial longitudinal strain was significantly higher in group 1 than in group 2 (34.48±9.73 to 26.27±7.41, p=0.019). There were no significant differences between other echocardiographic parameters. CONCLUSION: Our results suggest that left atrial longitudinal strain is associated with stroke severity during admission in patients with acute ischemic stroke. Left atrial longitudinal strain is an indicator of left atrial myocardial function.